FRI0311 Neuropsychiatric Lupus: Combining Advanced Morphometric Methods, Diffusion Tensor Imaging and Conventional MRI Leads To The Pathways of Brain Abnormalities. Correlation with Clinical and Laboratory Data. (15th July 2016) - Sarbu, M.I.; Toledano, P.; Calvo, A.; Sarbu, N.; Roura, E.; Espinosa, G.; Lladό, X.; Cervera, R.; Bargallό, N.
Abstract : Objectives: To combine conventional and advanced magnetic resonance imaging (MRI) to describe brain abnormalities in neuropsychiatric (NP) systemic lupus erythematosus (SLE), and to correlate them with clinical data. Methods: Prospective study including patients presenting central primary NPSLE, non-NPSLE and healthy controls (HC) undergoing brain MRI at 3T in 2014–2015. Conventional MRI data using visual scales for atrophy and white matter (WM) lesions, brain volumetry (voxel-based morphometry and Freesurfer), and diffusion-tensor imaging (DTI) were analyzed. Group differences were correlated with clinical, laboratory and treatment data. Results: Twenty-eight females with NPSLE, 22 non-NPSLE and 20 HC, mean age around 40 years, were recruited. Conventional MRI showed brain atrophy in NPSLE (p=0.005). Total cortical volume was reduced in NPSLE compared to HC (p=0, 042). Non-NPSLE had a reduction of left temporal gray-matter (GM) volume compared to HC (p=0.028). NPSLE had a decrease of left frontal WM volume compared with HC (p=0.002). Corpus callosum was reduced in NPSLE compared to HC (p=0.033) and non-NPSLE (p=0.043). DTI showed increased diffusivity (mean, axial and radial: MD, AD, RD) in bilateral temporal WM (p<0, 010) and reduced fractional anisotropy (FA) in right frontal WM (p=0.018) in NPSLE versus HC. SLEDAI score was correlated with atrophy (p=0.046); negatively with left temporal cortex volume (p=0.029) and with FA in WM hippocampal regions (p=0.002 left, p=0.048 right). SLICC score was correlated with diffusivity in bilateral temporal WM (MD:p=0.033; AD:p=0.039; RD:p=0.016) and right frontal WM (p=0.005); and negatively with FA in left WM hippocampal regions (p<0.001). SLE duration was correlated with diffusivity in temporal WM (MD:p=0.007; AD:p=0.007 and RD:p=0.007); and negatively with FA in right frontal and left temporo-occipital WM (p<0.0005 and p=0.014) and with right frontal cortex volume (p=0.028). Low C4 and CH50 were inversely correlated with left temporal cortex volume (p=0.003 and 0.002). Antimalarials were negatively correlated with atrophy on conventional MRI (p=0.004), total GM volume (p=0.021) and subcortical GM volume (p=0.020); specifically with right and left frontal cortex (p=0.029 and 0.015) and right and left thalamus (p=0.009 and 0.047). Antimalarials were correlated with lower diffusivity in multiple WM clusters (right and left temporal: decreased MD, p=0.006 and 0.004; AD, p=0.007 bilaterally; RD, p=0.005 bilaterally; and right frontal: decreased RD, p=0.010). Conclusions: Atrophy and DTI changes indicating microstructural damage in frontal and temporal white and gray matter are the most important radiological findings in NPSLE. Assessing them should become the milestone of monitoring this disease. This changes correlates with the severity, activity and duration of the disease. Antimalarial treatment could produce some protective effect on the brain in SLE patients. Disclosure of Interest: None declared